AN ANALYSIS OF FIGURATIVE LANGGUAGE TRANSLATION IN SIDNEY SHELDON'S NOVEL: "ARE YOU AFRAID OF THE DARK" - WIRANTO, Bambang (2007)
This research paper entitled "An Analysis of Figurative Language Translation in Sidney Sheldon's Novel: Are You Afraid of The Dark?" attempted to answer the two questions as follow; 1) What kinds of figurative language are translated in the novel?; 2) What kinds of translation method are applied by the translator in translating the figurative language? In conducting this research, the researcher used descriptive qualitative method. The data were 118 sentences that contains figurative languages. The research findings showed that there were twelve figurative language found in the novel. Personification is the most frequent figurative language used by the SL writer. The underlying reason for this is the SL writer intended to make the story seems more real and make the story more imaginative in the reader's perspective. In terms of the method used, communicative translation is the most frequent method of translation applied by the translator since it attempts to render the exact contextual meaning of the original in such a way that both content and language are acceptable and comprehensible to the reader.